Implementasi Kegiatan Mengajar Melalui Program Surabaya Mengajar Untuk Mengasah Mahasiswa Dalam Keterampilan Berfikir Dan Bekerja Sama Pada Bidang Pendidikan - Cindy Rahmawati (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Abstract. Real Work Lecture (KKN) is one of the activities that must be carried out by all students of the University of 17 August 1945 Surabaya to apply the knowledge they have acquired while sitting on the lecture bench as well as a concrete form of community service. Devotion to society the author does with the "title". The Surabaya Teaching Program is a form of program that is converted to Real Work Lectures. This program aims to improve competency for students in literacy and numeracy so that they are better prepared and more relevant to the times as future leaders of the nation who are superior and have personality. Through this program, students are opened as widely as possible to enrich and improve their insights and competencies in the real world. SMP Negeri 39 Surabaya is the place of choice for the writer to do a form of community service through the school's students. Real Work Lecture, Teaching, Administration